2009
DOI: 10.1371/journal.ppat.1000529
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Identification of Salmonella enterica Serovar Typhimurium Genes Required for Infection of BALB/c Mice

Abstract: Genes required for infection of mice by Salmonella Typhimurium can be identified by the interrogation of random transposon mutant libraries for mutants that cannot survive in vivo. Inactivation of such genes produces attenuated S. Typhimurium strains that have potential for use as live attenuated vaccines. A quantitative screen, Transposon Mediated Differential Hybridisation (TMDH), has been developed that identifies those members of a large library of transposon mutants that are attenuated. TMDH employs custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 59 publications
(64 reference statements)
5
100
0
Order By: Relevance
“…We explored whether Salmonella metabolic requirements for the systemic infection of mice were comparable with the metabolic requirements for fitness within tomatoes. We retrieved data from previous work using transposon insertion libraries in Salmonella enterica serovar Typhimurium (37,38) that had been applied in a mouse model for systemic infection and compared them with our results from the Salmonella-tomato interaction. A total of 327 KEGG Orthology (KO) identifiers were mapped for the genes required for persistence in tomatoes, and 505 KO identifiers required for systemic infection of mice were mapped.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We explored whether Salmonella metabolic requirements for the systemic infection of mice were comparable with the metabolic requirements for fitness within tomatoes. We retrieved data from previous work using transposon insertion libraries in Salmonella enterica serovar Typhimurium (37,38) that had been applied in a mouse model for systemic infection and compared them with our results from the Salmonella-tomato interaction. A total of 327 KEGG Orthology (KO) identifiers were mapped for the genes required for persistence in tomatoes, and 505 KO identifiers required for systemic infection of mice were mapped.…”
Section: Resultsmentioning
confidence: 99%
“…in the interaction with tomatoes, scavenging of amino acids was required in the systemic mouse infection. Transposon disruptions in just a few pathways (e.g., the urea cycle) impaired Salmonella fitness during systemic infection (37,38). Besides being involved in the synthesis of arginine, the urea cycle is also involved in the incorporation of excess nitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…atpA mutants of S. Typhimurium are strongly attenuated and confer protection against subsequent infections [4, [114][115][116]. The development of regulated, delayed attenuated mutants has further helped in combating this problem.…”
Section: Current Prophylaxis and Treatmentmentioning
confidence: 99%
“…Screening of transposon mutant libraries indicated that insertions in STM0084 did not have a strong impact on competitiveness of the mutant strains in in-vivo assays with mice injected with mutants and wild type (Chaudhuri et al 2009), but when chickens, cattle and pigs were infected orally with the transposon mutants, mutants with insertions in STM0084 were less competitive (Chaudhuri et al 2013 In an attempt to further our understanding of the role of aslA and its potentially differential regulation in S. e. Enteritidis Nal R and Kentucky 3795, the gene was deleted in the current study and the utilization of sulfate ester compounds by the mutant and wild-type strains was assayed. The competitiveness of the mutants versus the wild-type strains in cell-invasion assays was also determined.…”
mentioning
confidence: 99%